Asymmetric and regime switching behaviour of GDP and energy nexus in India: new evidences. Issue 1 (2nd January 2021) - Kanjilal, Kakali; Ghosh, Sajal
ABSTRACT: This study revisits the relationship between energy and electricity consumption with economic activity for India applying threshold vector error correction model and non-linear ARDL methods to explore their regime-driven and asymmetric dynamics for the period 1971 to 2014. The presence of threshold cointegration in the underlying relationship indicates that the nonlinear dynamics are divided into 'normal' and 'extreme' regimes. A normal regime advocates the validity of growth and feedback hypothesis for economic activity with energy and electricity consumption, respectively. But an extreme regime supports the conservation hypothesis. An asymmetric cointegrating relationship further corroborates the findings. Finally, the study proposes some actionable policy prescriptions.